2015
DOI: 10.1080/10408398.2015.1038377
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effect of Hydrolyzed Collagen on Bone Metabolism

Abstract: Osteoporosis is a chronic and asymptomatic disease characterized by low bone mass and skeletal microarchitectural deterioration, increased risk of fracture, and associated comorbidities most prevalent in the elderly. Due to an increasingly aging population, osteoporosis has become a major health issue requiring innovative disease management. Proteins are important for bone by providing building blocks and by exerting specific regulatory function. This is why adequate protein intake plays a considerable role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 111 publications
(77 reference statements)
1
69
0
Order By: Relevance
“…The beneficial anabolic effect of PTH administration on bone in various animal models and humans has been proved [ 8 ]. However, it has been emphasized that compliance to such therapy tends to be poor and benefit does not continue after ending treatment [ 9 ]. Besides, the long-term application of anti-osteoporotic drugs comes with serious side effects [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial anabolic effect of PTH administration on bone in various animal models and humans has been proved [ 8 ]. However, it has been emphasized that compliance to such therapy tends to be poor and benefit does not continue after ending treatment [ 9 ]. Besides, the long-term application of anti-osteoporotic drugs comes with serious side effects [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the major structural element in the extracellular matrix of all connective tissues, collagens represent about 80% of the total protein [ 13 ]. Collagens form the scaffold for the attachment of cells and the anchorage of macromolecules and minerals [ 9 ]. Furthermore, bone collagens can bind and store growth factors and cytokines, such as insulin like growth factor (IGF) I and II, which are released during bone degradation and in turn promote bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous scientific studies reported that osteoporosis has become a major health issue. Proteins more specifically collagen, plays a considerable role in both bone development and bone maintenance [46,47]. Here, the Biofield Energy Treated vitamin D 3 significantly improved the level of collagen which might be helpful to maintain a healthy bone in postmenopausal women selectively.…”
Section: Assessment Of Collagen Activitymentioning
confidence: 99%
“…Collagen, the source of fibers is the most abundant constituent of all the connective tissue. Various evidence reported that collagen, plays a considerable role in both bone development and bone maintenance [45,46]. ATF4, a transcription factor that stimulates amino-acid uptake and collagen synthesis in osteoblast.…”
Section: Assessment Of Collagen Activitymentioning
confidence: 99%